Intangible, invisible and eternally nascent: Designing sound in Australian performing arts. Issue 1 (1st December 2021) - Alsop, Roger
This article is primarily focused on sound design in the performing arts. While scenography is usually defined as the visual/object elements of a performance design, it is often discussed as including all of the heard and seen elements: sound, costume, lighting, sets, props and projections. The intention is that these elements work synergistically to create a 'whole-more-than-the-sum-of-its-parts', with scenography considered a wholistic discipline that embraces many aspects to support the intentions of the creators and the performers in a performance. Scenographic designers provide bespoke or unique solutions required to do this across specific briefs and budgets. While the discussion here centres on sound design for performance in Melbourne, it is intended to apply more broadly, particularly in developing a more complementary, integrated approach to sound in scenography, and regarding education and processes. This is to encourage a more global and inclusive consideration of the topic ‐ to develop discussion, and therefore potential ‐ of the manifold interrelationships in scenographic design in the performing arts. While there is no attempt to explicitly answer a key question or propose a defined theory, this discussion intends to illuminate various issues in sound design for performing arts in order to develop conceptual and practical approaches that enhance the collaborations and synergies possible in scenography for performing arts, ensuring that the whole is indeed more than the sum of its parts.